Motivation and Attitude towards Studying Tourism among Students of Kaski District, Nepal - Palikhe, Amin; Adhikari, Nabin Bahadur; Mulmi, Sudan Kumar (Janapriya Journal of Interdisciplinary Studies, 2019)
This study aimed to find the factors that motivate students to study tourism in the colleges of Nepal and to identify selection patterns for studying tourism subject through analysis of socio demographic determinants according to gender, study level and college type. This study is designed as a descriptive and analytical study based on primary data. A total of 124 respondents collected from Kaski district as data input during November 2018 and data are collected using structure questionnaire. Chi-square test is used to determine factors associated with studying tourism in colleges of Nepal according to gender, study level and college type. Cronbach’s alpha has been used to test reliability and validity. The result shows that gender has no association with all motivational variables for studying tourism in colleges of Nepal. Study level is associated with motivational variables such as learning value, self-efficacy, interest and emerging subject. College type is associated with motivational variables such as learning value, self-efficacy, social status and interest (p<0.05). This study is particularly relevant for tourism subject teaching colleges and can help them for developing strategies for promotion of tourism subjects. Colleges studying tourism subjects must focus on the various opportunity areas that can be achieve by studying tourism subject to attract students.